To the 100th anniversary of birth of Georgy Antonovich Gamov (Вопросы атомной науки и техники, 2004)
GEORGY ANTONOVICH GAMOV (b. March 4, 1904, Odessa, Ukraine, d. Aug. 19,
1968, Boulder, U.S), physicist and cosmologist who was one of the foremost advocates of the big-bang theory, according to which the universe was formed in a colossal explosion billions of years ago. In addition, his work on deoxyribonucleic acid (DNA) made a basic ontribution to modern genetic theory.